1998
DOI: 10.1111/j.1469-7793.1998.495bh.x
|View full text |Cite
|
Sign up to set email alerts
|

ATP is a potent stimulator of the activation and formation of rodent osteoclasts

Abstract: There is increasing evidence that extracellular ATP acts directly on bone cells via P2 receptors. In normal rat osteoclasts, ATP activates both non‐selective cation channels and Ca2+‐dependent K+ channels. In this study we investigated the action of ATP on the formation of osteoclasts and on the ultimate function of these cells, namely resorption pit formation. We found that ATP stimulated resorption pit formation up to 5.6‐fold when osteoclast‐containing bone cell populations from neonatal rats were cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 23 publications
7
100
0
Order By: Relevance
“…Prostaglandins also stimulate osteoclast formation (Collins and Chambers, 1992;Lader and Flanagan, 1998), and commonly mediate hypoxic responses in other cell types, such as macrophages (Lewis et al, 1999). Secondly, hypoxia stimulates purine nucleotide release from endothelial cells (Bodin and Burnstock, 1995), and we have previously shown that ATP and ADP are powerful osteolytic agents, acting through P2 receptors on bone cells (Morrison et al, 1998;Hoebertz et al, 2000Hoebertz et al, , 2001; this mechanism could account for some of the resorptive action of hypoxia in intact bone but it remains to be investigated whether nucleotide release from other cell types in bone might also be enhanced by low PO 2 . Thirdly, one of the major effects of hypoxia on cells is to stimulate the production of potent angiogenic factors such as VEGF, tumor necrosis factor-a, and fibroblast growth factors (Lewis et al, 1999); these factors are also stimulators of the formation and/or function of osteoclasts (Simmons and Raisz, 1991;Nakagawa et al, 1999Nakagawa et al, , 2000Suda et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins also stimulate osteoclast formation (Collins and Chambers, 1992;Lader and Flanagan, 1998), and commonly mediate hypoxic responses in other cell types, such as macrophages (Lewis et al, 1999). Secondly, hypoxia stimulates purine nucleotide release from endothelial cells (Bodin and Burnstock, 1995), and we have previously shown that ATP and ADP are powerful osteolytic agents, acting through P2 receptors on bone cells (Morrison et al, 1998;Hoebertz et al, 2000Hoebertz et al, , 2001; this mechanism could account for some of the resorptive action of hypoxia in intact bone but it remains to be investigated whether nucleotide release from other cell types in bone might also be enhanced by low PO 2 . Thirdly, one of the major effects of hypoxia on cells is to stimulate the production of potent angiogenic factors such as VEGF, tumor necrosis factor-a, and fibroblast growth factors (Lewis et al, 1999); these factors are also stimulators of the formation and/or function of osteoclasts (Simmons and Raisz, 1991;Nakagawa et al, 1999Nakagawa et al, , 2000Suda et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…ATP, acting via P2Y receptors, was shown to inhibit non-quantal ACh release at the neuromuscular junction of mouse [43,44]. Later, it was identified that activation of the P2Y 12 and P2Y 13 receptors, as well as adenosine A 1 receptors, inhibited ACh release from mammalian motor nerve terminals [45]. The role of P2Y receptors ATP is released during neurotransmission and, after breakdown to adenosine, acts on presynaptic P1 (A 1 ) receptors to inhibit release of ACh.…”
Section: Skeletal Neuromuscular Junctionmentioning
confidence: 99%
“…Originally, this effect was proposed to be mediated via the P2Y 2 receptor; however, in a follow-up study, UTP failed to stimulate resorption suggesting this was not the case [259]. Subsequently, ATP was found to stimulate the formation and activity of rodent osteoclasts, effects which were inhibited by apyrase or suramin [12]. These stimulatory actions on resorption were further increased when osteoclasts were first activated by culture in acidified medium [12].…”
Section: Functional Effects Of P2 Receptor-mediated Signalling In Ostmentioning
confidence: 99%
See 2 more Smart Citations